EP365 Prognosis factors in patients with early cervical cancer. (1st November 2019) - Montero Macías, R; Bonsang-Kitzis, H; Balaya, V; Ngo, C; Deloménie, M; Koual, M; Nguyen-Xuan, H-T; Bats, A-S; Lecuru, F
Abstract : Introduction/Background: Many factors for recurrence have been described in patients with early cervical cancer (ECC). Lymph node involvement is considered the main prognostic factor. Different factors had been associated for risk to involvement lymph pelvic nodes and also with recurrences: FIGO stage, lymphovascular space involvement (LVSI), tumor grade and size of primary tumor. We studied different risk factors to involvement lymph pelvic node and to recurrence in our population. Methodology: We retrospectively analysed 85 patients with ECC treated between 2004–2018. Inclusion criteria: patients with ECC (stage IA1–IIA). Exclusion criteria: insufficient follow-up (<6 months), not node stage evaluation and neoadjuvant radiochemotherapy. No patients with stage FIGO IA had recurrences, so no included in analyse. Simple logistic regression analyses were performed, expressed as odds ratio (OR) and 95% confidence interval (CI). P values were significance <0.05. Survival data were analysed using Kaplan-Meier-curves and log-rank-test. Results: The univariate analysis revealed a relationship between tumor size and risk of recurrences (OR 8, 37; 95% CI 2, 24–40, 8; p 0, 003). No relationship was revealed with the others variables with recurrences and any variables had relationship with the risk of pelvis node metastasis. There was no statistically significant difference in disease-free survival relative to analyzed prognostic factors in ECC stages, except for tumor size (p<0, 001 Log-Rank). Conclusion: We don't found risk factors for pelvic lymph node metastasis. Only tumor size is a prognosis factor and have impact in progression-free survival. We don't found relation between other factors described previously like stage, node metastasis, LVSI and recurrences. Size is a significant and major prognostic factor in cervical cancer, regardless of the type of treatment utilized. The new FIGO staging 2018 system for cervical cancer with the inclusion of size ³ 20 mm for Stage IB2 cancers better reflects survival and overall prognosis. Disclosure: Nothing to disclose.